Macbeth - Shakespeare, William (Oxford University Press, 2006)
A dark, rainy day in Scotland, long ago. Returning from battle, Macbeth and his friend Banquo meet three witches. Macbeth, the king! they say, but Macbeth is not a king, he is just a simple soldier. Macbeth and Banquo cannot forget the witches' words. Soon Macbeth is king, but his wife walks in her sleep at night, and dreams of blood. What lies in the future for Banquo? And how many people must die before Scotland finds peace once more?